Problem of acoustical relaxation of lutidine 3-4 - LINDE, B.; ROSENFELD, E. (Archives of Acoustics, 1989)
In this paper the results of acoustical absorption measurements in frequency range from 300 kHz to 9 GHz for lutidine 3-4 are presented. An acoustical relaxation process in the low frequency range between 0.3-10 MHz was observed. The relaxation process which has been noticed can be explain as a phenomenon of association and dislocation of sandwich molecules.